2011
DOI: 10.1152/japplphysiol.01333.2010
|View full text |Cite
|
Sign up to set email alerts
|

Can muscle size fully account for strength differences between children and adults?

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
0
25
0
1
Order By: Relevance
“…It is well known that muscle strength increases during maturation (O'Brien et al., 2010b). Although still under debate, it is likely that this increase is mainly due to increases in muscle size (especially the PCSA), moment arm length and activation level and not changes in muscle specific contractile capacity (Bouchant et al., ). In the present study, the maximal knee extensor moments did not differ between the adolescent and middle‐aged athletes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that muscle strength increases during maturation (O'Brien et al., 2010b). Although still under debate, it is likely that this increase is mainly due to increases in muscle size (especially the PCSA), moment arm length and activation level and not changes in muscle specific contractile capacity (Bouchant et al., ). In the present study, the maximal knee extensor moments did not differ between the adolescent and middle‐aged athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research suggests that increases in muscular strength are a result of muscle cross-sectional area, architectural (muscle size, moment arm length) and neural (voluntary activation level) adaptations 53 186. However, the mechanisms appear to differ according to the stage of development and are tissue dependent (ie, muscle vs tendon).…”
Section: Effectiveness Of Youth Resistance Training For the Developmementioning
confidence: 99%
“…The role of quantitative factors (i.e., muscle mass and muscle moment arm) has been advocated (38,46), but the implication of qualitative factors (e.g., nervous factors) remains unclear (7,46). Indeed, some studies have shown that even when muscle strength is normalized to muscle dimensions, differences between children and adults may persist (46).…”
mentioning
confidence: 99%